Drug-induced bone disorders: A systematic review - Anshita Aggarwal; Meha Sharma; Indira Maisnam; Soumitra Ghosh; Sameer Aggarwal; Saptarshi Bhattacharya; Deep Dutta (Indian Journal of Rheumatology)
Drug-induced bone disorders are a group of disorders characterized by osteomalacia or osteoporosis, with the common denominator being the iatrogenic nature of the disease. Drug-induced bone disorders are either due to the drug directly effecting the bone microarchitecture (osteoblastic or osteoclastic activity) or indirectly by interfering with Vitamin D metabolism, Vitamin D/calcium absorption, and excess calcium loss or due to altered hormone states which promote bone loss (hypogonadism, hyperthyroidism, somatostatin excess states, insulin deficiency, increased systemic inflammation, and oxidative stress). References for this review were identified through searches of PubMed, Medline, and Embase for articles published until July 2019 using the terms “drug induced bone disorders” (MeSH Terms) AND “osteoporosis” (All Fields) OR “osteomalacia” (All Fields). Anti-epileptics, proton pump inhibitors, glucocorticoids, immunosuppressants (calcineurin inhibitors), anticoagulants, glitazones, SGLT2 inhibitors, somatostatin analogs, anticancer medications, and protein kinase inhibitors are some of the commonly used medications associated with bone mineral loss. An increased awareness, minimizing the use of these medications in patients at increased risk of fractures, keeping dosage and duration of therapy to the lowest, ensuring Vitamin D and calcium adequacy either through diet or supplements, and prophylactic use of bisphosphonates (where indicated) can play a major role in preventing morbidity associated with drug-induced bone disorders.